Blogs in the mainstream media : an exploration of a code of ethical conduct for j-bloggers at Die Burger Western Cape - De Vries, Florence (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MPhil (Journalism))--University of Stellenbosch, 2008.